Contribution of STIM-Activated TRPC-ORAI Channels in Pulmonary Hypertension Induced by Chronic Sustained and Intermittent Hypoxia - Castillo-Galan, Sebastian; Arenas, German A.; Iturriaga, Rodrigo (My University, 2022)
Sustained and intermittent hypoxia produce vasoconstriction, arterial remodeling, and hypertension in the lung. Stromal interaction molecule (STIM)-activated transient receptor potential channels (TRPC) and calcium release-activated calcium channel protein (ORAI) channels (STOC) play key roles in the progression of pulmonary hypertension in pre-clinical models of animals subjected to sustained and intermittent hypoxia. The available evidence supports the theory that oxidative stress and hypoxic inducible factors upregulate and activate STIM-activated TRPC-ORAI Ca2+ channels, contributing to the pulmonary remodeling and hypertension induced by sustained hypoxia. However, less is known about the effects of oxidative stress and hypoxic inducible factors on the modulation of STIM-activated TRPC-ORAI channels following chronic intermittent hypoxia. In this review, we examined the emerging evidence supporting the theory that oxidative stress and hypoxic inducible factors induced by intermittent hypoxia upregulate and activate STIM-activated TRPC-ORAI Ca2+ channels. In addition, we used bioinformatics tools to search public databases for the genes involved in the upregulation of STIM-activated TRPC-ORAI Ca2+ channels and compare the differential gene expression and biological processes induced by intermittent and sustained hypoxia in lung cells.
Keywords: sustained and intermittent hypoxia; hypoxia-inducible factor; oxidative stress; obstructive sleep apnea; pulmonary hypertension; store-operated channels